Peculiarities of adaptation of albanian students in the russian high school - A Aliajdaraj (Peoples' Friendship University of Russia (RUDN University), 2010)
In this article are analyzed different approaches of the intercultural adaptation and are revealed acute specific details of the structure of adaptation among Albanian students during the time of living in Moscow.